Macroeconomic Impact of HIV/AIDS in Nigeria: Error Correction Modelling Approach - Dauda, Rasaki Stephen; Olaniyan, Olanrewaju (Advances in Social Sciences Research Journal, 2017)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) constitutes a heavy and severe burden on the population health status and the economies of the affected countries. Nigeria’s HIV/AIDS epidemic is generalized, with the country having the second highest burden of the disease in the world after South Africa. This study employed the Error Correction Modeling (ECM) approach to determine how HIV/AIDS affects the growth of the economy of Nigeria, using time series data covering the period 1980-2010. The findings showed that HIV/AIDS has a negative and significant effect on the growth of the economy of Nigeria. The coefficients of HIV incidence and its lag stood significantly at -0.57 and -0.63 respectively. The ECM variable was rightly signed, showing a negative and statistically significant coefficient of 0.19, an indication of a 19% speed of convergence to equilibrium in the long run. The adjusted R-Squared of 81% suggests that the regressors explained a high proportion of variation in economic growth. The findings of the study imply that HIV/AIDS is capable of reducing economic growth in Nigeria. Therefore, its spread should be properly checked.